Implementation of Encrypt National ID Card in Sinovi Application Use Waterfall Methodology - Teguh Rijanandi; Ayu Silvia; Bintang Abillah Safna; Rima Dias Ramadhani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
In this era of increasingly rapid technology, the development of information systems is also growing rapidly, because information systems provide what users need. Information is a very valuable thing. When information or data falls into irresponsible hands, it will bring disaster to the owner, and there have been many cases of data leaks in the past that have harmed several parties. There are various ways to protect data or information. Therefore, data security techniques are needed, the message security process is very diverse, including using cryptography. Cryptography aims to scramble messages so that they are difficult to read by unauthorized parties. In this study, we will use the AES 256 encryption method with the waterfall research method to secure KTP images on the Sinovi application, Sinovi is a copyright registration application at the Telkom Institute of Technology Purwokerto. The results of this study are the AES method will convert data or information in the form of plain text into cipher-text then stored in a file to replace the image file so that in this way the image cannot be viewed directly because it must pass the decryption technique first and the research data will be presented. in a table of blackbox testing. It is hoped that a security system like this can protect data from unauthorized parties and further research is expected to have research that tests AES 256 with different methods. https://github.com/teguh02/T-Encryption